Ammonia Decomposition over Ru/SiO2 Catalysts - Lee, Ho Jin; Park, Eun Duck (Catalysts, 2022)
Ammonia decomposition is a key step in hydrogen production and is considered a promising practical intercontinental hydrogen carrier. In this study, 1 wt.% Ru/SiO2 catalysts were prepared via wet impregnation and subjected to calcination in air at different temperatures to control the particle size of Ru. Furthermore, silica supports with different surface areas were prepared after calcination at different temperatures and utilized to support a change in the Ru particle size distribution of Ru/SiO2. N2 physisorption and transmission electron microscopy were used to probe the textural properties and Ru particle size distribution of the catalysts, respectively. These results show that the Ru/SiO2 catalyst with a high-surface area achieved the highest ammonia conversion among catalysts at 400 °C. Notably, this is closely related to the Ru particle sizes ranging between 5 and 6 nm, which supports the notion that ammonia decomposition is a structure-sensitive reaction.
Keywords: ammonia decomposition; calcination temperature; hydrogen production; Ru/SiO2